Directed evolution of Candida antarctica lipase A using an episomaly replicating yeast plasmid - Sandström, Anders G.; Engström, Karin; Nyhlén, Jonas; Kasrayan, Alex; Bäckvall, J.-E. (Protein Engineering, Design and Selection, 2009)
We herein report the first directed evolution of Candida antarctica lipase A (CalA), employing a combinatorial active-site saturation test (CAST). Wild-type CalA has a modest E- value of 5.1 in kinetic resolution of 4-nitrophenyl 2-methylheptanoate. Enzyme variants were expressed in Pichia pastoris by using the episomal vector pBGP1 which allowed efficient secretory expression of the lipase. Iterative rounds of CASTing yielded variants with good selectivity toward both the ( S )- and the ( R )-enantiomer. The best obtained enzyme variants had E -values of 52 ( S ) and 27 ( R ).